Analisis Beban Kerja Fisik Dan Mental Untuk Mengurangi Tingkat Kelelahan Pekerja Di CV. Sumber Jaya Furniture - Prasetya, Yoga Dwi; , Dr. Suranto, MM (2016)
This study aims to analyze the workload experienced by all workers in the CV. Sumber Jaya Furniture. The subjects were all workers of 20 people. The workload is measured is the physical and mental workload. Physical load analysis method used in this study is based on the Cardiovascular Load (CVL). While the method of analysis of mental load used in this study is a NASA-Task Load Index (NASA TLX). The benefits of this research is Knowing how big the physical and mental workload experienced by workers at work 8 hours. Based on analysis of the Cardiovascular Load (CVL), the operator who received the heaviest physical workload is a machine operator 3 with a percentage of Cardiovascular Load (CVL) amounted to 30.18%, which means the need for improvement. While the results of the analysis of the NASA-Task Load Index (NASA TLX) operators who receive mental workload is heaviest operator Office, plaiting 1 and Packing with each WWL index of 81. Proposed improvements by which the chair design in the machine 3, and the provision of music on the carrier Office, plaiting 1 and Packing as well as additional time off. After the proposal was held on the results of the physical burden Cardiovascular Load (CVL) received at the machine operator 3 to 21.05%. While the mental burden of the results of the NASA-Task Load Index (NASA TLX) received by the operator Office, plaiting and Packing received 1 respectively to 61, 64 and 64. Keywords: Workload, Cardiovascular Load, NASA TLX